First responders : inside the U.S. strategy for fighting the 2007-2009 global financial crisis - Bernanke, Ben; Geithner, Timothy F.; Paulson, Henry M., 1946-; Liang, J. Nellie (Jean Nellie) (Yale University Press, 2020)
Faced with the prospect of a new Great Depression in 2008 when the collapse of Lehman Brothers set off a global panic, the Treasury Department, the Federal Reserve, the Federal Deposit Insurance Corporation, and other agencies took extraordinary measures to contain the damage and steady the financial system and the economy. Edited by three of the policymakers who led the government's response to the crisis, with chapters written by the teams tasked with finding policy solutions, this book provides a comprehensive accounting of the internal debates and controversies surrounding the measures that were taken to stabilize the economy.